Counterclaim in Investment Arbitration as an Instrument for Protection of the Environment - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The paper considers the possibility for respondent states in investment arbitration to use the counterclaim as an instrument for establishing responsibility of the investor for infringement of the environment. The analysis is directed towards the two most significant obstacles in this regard. The first is the issue of whether the investor has, by commencing arbitration against the host state, consented to the jurisdiction of the arbitral tribunal for issues raised in the counterclaim. The practice of those tribunals shows that the problem is particularly complex with regard to the interpretation of the close connection requirement for admissibility of the counterclaim, i. e. the requirement that there is a connection between the dispute in question and claims raised by the respondent state. Furthermore, apart from the problem of jurisdiction and admissibility of the counterclaim, the respondent state is faced with the potential lack of its normative basis. This is the issue of whether the legal rules applied by the tribunal to the merits of the dispute contain an obligation owed by the investor and whether the infringement of that obligation would constitute a basis for submission of a counterclaim.